Energy-Efficient Retrofitting Strategies for Research Laboratory Buildings: Case Study at the University of Utah - Aksamija, Ajla; Milosevic, Suncica; Adekunle, Timothy (Enquiry The ARCC Journal for Architectural Research, 2025)
This research study examined building performance and retrofitting strategies for reducing energy consumption in existing research laboratories. Research laboratory buildings are one of the most energy-intensive building typologies due to their high energy demands, complex building systems, and significant loads for mechanical cooling and ventilation. Retrofitting may extend building lifespan and improve their performance, energy consumption, carbon footprint, and occupants’ comfort. The study examined an existing research laboratory building at the University of Utah campus, utilizing a combination of research methods, such as archival and observational studies, field measurements, building envelope and HVAC systems assessment, and whole-building energy modeling and simulations. Actual energy consumption data was collected for three years and compared against simulated data. Five different retrofitting options were considered, where four options represented low-impact retrofits (improvements to the building envelope and interior lighting) and one option represented a deep-impact retrofit (improvements to the building envelope, interior lighting, and HVAC systems). These investigated retrofit options were simulated and compared to the building’s actual and simulated energy consumption data. The results show that the deep-impact retrofit option would have the highest impact on energy use savings (more than 50% energy savings), while the four low-impact retrofit options would have lower, but comparable results (between 22% and 27% energy savings). Therefore, improvements to the mechanical systems are necessary to significantly reduce energy consumption and the associated carbon footprint of existing research laboratory buildings, besides building envelope and lighting improvements.